Lorsbach model (E5) On cognitive achievement and its impact In learning some of basic skills in football halls - Layedh Abdulkareem, Saad (International Journal of Psychosocial Rehabilitation, 2020)
Cognitive achievement is one of the most important processes that have a large and positive role through its association with physical education, and that the educational field has reached a level of development as a result of the great challenges faced by education, perhaps the most prominent of which is the so-called cognitive explosion, and through what the above shows the importance of this type of models represented With the model ((Lorsbach)) in the educational process, in which the student has a positive role in increasing achievement, especially knowledge and skill, including the basic skills of gymnasium football, which are (passing, extinguishing, and rolling) . The researcher noticed that there is a decline in the skill performance of female students of the College of Physical Education and Sports Sciences, and the researcher found that everyone (teachers and professors) uses certain methods in training without diversifying or changing the matter that causes boredom and boredom for students The students ’skills were deteriorating, and the grades were seen for the students, so the most general was poor. Therefore, the researcher took it upon himself to find a model through which students acquire skills in a good and ideal manner and according to the constructive theory where the Lorsbach model was chosen. The use of the curriculum is one of the most important ways to solve the problem, so the researcher used the experimental approach (with two equal groups) and the two tests (pre and post) . One female student for each division (20) students were divided into two control and experimental groups, and each group had (20) students, and the researcher used the following tests for some basic skills in football for halls on the students (passing, putting out, rolling) in addition to conducting a cognitive achievement test for all its steps.